T-cell Homing Therapy for Reducing Regulatory T Cells and Preserving Effector T-cell Function in Large Solid Tumors - Hu, Jiemiao; Sun, Chuang; Bernatchez, Chantale; Xia, Xueqing; Hwu, Patrick; Dotti, Gianpietro; Li, Shulin (Clinical cancer research, 2018)
Purpose: Infused autologous tumor-infiltrating lymphocytes (TIL) and tumor-targeted chimeric antigen receptor (CAR) T cells typically surround malignant lesions or penetrate small tumor nodules but fail to penetrate large solid tumors, significantly compromising their antitumor impact. Strategies to overcome this primary challenge are largely required. Experimental Design: We tested the effects of IL12 plus doxorubicin on T-cell penetration and efficacy in solid tumors in a murine lung cancer model, a murine breast carcinoma lung metastasis model, and two human xenograft tumor models bearing large tumors (>10 mm). Results: Intriguingly, this simple approach increased the numbers, the distribution, and the depth of penetration of infused CD8+ T cells in these tumors, including both TILs and CAR T cells. This combined treatment halted tumor progression and significantly extended survival time. Studies of the underlying mechanism revealed multiple effects. First, the combined treatment maintained the high ratios of immune-stimulatory receptors to immune-inhibitory receptors on infiltrated CD8+ T cells, reduced the accumulation of immunosuppressive regulatory T cells, and enhanced the numbers of T-bet+ effector T cells in the tumors. Second, doxorubicin induced chemokines CXCL9 and CXCL10, which may attract NKG2D+CD8+ T cells to tumors, and this effect was boosted by IL12-induced IFNγ accumulation in tumors, promoting the penetration of NKG2D+CD8+ T cells. Conclusions: The deep penetration of infused T cells associated with combined IL12 plus doxorubicin yielded striking therapeutic effects in murine and human xenograft solid tumors. This approach might broaden the application of T-cell therapy to a wider range of solid tumors. Clin Cancer Res; 24(12); 2920–34. ©2018 AACR. See related commentary by Berraondo et al., p. 2716